HUBUNGAN STATUS IMUNISASI DAN PENCEMARAN UDARA DENGAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS TOLANGOHULA KABUPATEN GORONTALO - Dewi Modjo; Lenny Ali (-, 2021)
The immunization activities conducted every month, while the problem is the implementation of immunitation in the social health centers of Tolangohula has not been achieved with UCI (Universal Child  immunization). The  purpose  of  the  this    research  was  to  determinate the  relationship of immunization and air pollution with the incedence of ISPA to baby in the social health centers of Tolangohula.The analiyze of the data that used in this research is the analiysis of univariate anad analiysis of bivariate. Based on the results of this research concluded that (a) the immunization status and air pollution related with the incidence of ISPA to baby in the social health centers of Tolangohula. (b) has a relationship of significant between  immunization status and air pollution with incidence of ISPA to baby in the social health centers of Tolangohula.